How Safety Knowledge and Work Environment Affect Workplace Accidents: Uncovering the Role of Safety Behaviors - Marcia, Marcia; Kusumapradja, Rokiah; Silviana Mustikawati, Intan (Syntax Corporation Indonesia, 2024)
Workplace accidents in hospitals can arise from human or environmental factors, highlighting the necessity of implementing Hospital Occupational Safety and Health (HOSH) measures. Preliminary study at X Hospital shows that work-related accidents persist, with the majority leading to physical injuries. This study aims to observe the impact of HOSH knowledge and the work environment on nurse workplace accidents, with safety behaviors serving as a mediating factor. The research utilizes a quantitative survey method with a cross-sectional design. A total of 123 nurses participated in the study. An analysis using Structural Equation Modeling (SEM) was conducted to assess the statistical impact. The findings indicate that improving Occupational Safety and Health (OSH) knowledge and enhancing the work environment can significantly reduce workplace accidents. The mediating role of safety behaviors further amplifies this effect. Both HOSH knowledge and the work environment have a positive significant impact on safety behaviors, while HOSH knowledge, the work environment, and safety behaviors each have a negative significant impact on workplace accidents